If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6x + 1 = 0 Reorder the terms: 1 + 4x + 6x = 0 Combine like terms: 4x + 6x = 10x 1 + 10x = 0 Solving 1 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 10x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 10x = 0 + -1 10x = 0 + -1 Combine like terms: 0 + -1 = -1 10x = -1 Divide each side by '10'. x = -0.1 Simplifying x = -0.1
| x^2-5=sqrt(3*x) | | -23-2p=19-p | | 12x^2+35x-3=0 | | 7=9(2f+5) | | 3(2x+3)=4-x | | 4w-7=3w+1 | | x^2+18x+30=0 | | 4x-5=4x-9 | | 1/2n+5/6=2/3 | | (6x+2)+20=90 | | -8-7x-6x=-8 | | 18=a(a-7) | | 4x=14x-30 | | 6b+15=4b+19 | | -84=-7(x+5) | | (6x+2)+20=360 | | 20+.5= | | bing=-2 | | -20=-4x+-6x | | -5.6+12.2=5 | | 2x+3(2x-9)=(4x+3) | | (6x+2)+20=180 | | 5a+6=-8 | | 8x-2x+66=8x+26 | | 2y-4=-10x | | 5y-60332=600y+422 | | -7+2h=-15 | | 2(4b-6)+6(-3-2b)=6-4b+4-5b | | 3x+9=-6x+16 | | 4x+6=y-3 | | 8u+1=7u+1 | | 4k-2=k-6 |